Ehretia genus: a comprehensive review of its botany, ethnomedicinal values, phytochemistry, pharmacology, toxicology and clinical studies - Jiang, Sai; Wang, Mengyun; Kaur, Amanpreet; Jiang, Lin; Cai, Yuan; Luo, Jiangyi; Li, Minxi; Wang, Hongxing; Wan, Dan; Peng, Yanmei (Frontiers in Pharmacology, 2025)
BackgroundThe Ehretia genus, comprising 66 species in the Boraginaceae family, has a history of ethnomedicinal use for various ailments. This review focuses on the botany, traditional uses, phytochemistry, pharmacology, toxicology, clinical studies, cultivation, and commercial potential of the Ehretia genus, with the goal of enhancing current research and applications.MethodsLiteratures related to Ehretia species were compiled using keywords such as “Ehretia,” “traditional use,” “chemical constituents,” and “bioactivity” from scientific databases, including “China Knowledge Resource Integrated Databases (CNKI),” “Flora of China,” “Google Scholar,” “Hunan Library,” “Plants of the World Online,” and “Web of Science” and so on.ResultsFrom 1980 to August 2024, only 101 compounds have been identified within this genus, primarily consisting of flavonoids, phenylpropanoids, phenolics, benzoquinones, triterpenoids, and fatty acids, with phenylpropanoids being the main components. Extracts and compounds from Ehretia species exhibited various bioactivities, including antioxidant, hepatoprotective, analgesic, anti-inflammatory, antibacterial, and anticancer effects, etc.ConclusionResearch on the Ehretia genus is limited, with many species remaining underexamined in terms of phytochemistry and pharmacology. Few active compounds have been isolated and assessed for biological activities, and there is a lack of investigation into their mechanisms of action. Despite its documented uses, Ehretia species remains less explored scientifically than other Boraginaceae genera, presenting significant research opportunities. Further comprehensive studies are necessary to deepen our understanding of this diverse genus and validate its therapeutic potential.